Developing a model for strategic agility in knowledge-based companies using a mixed methods approach - Asma Soltaninezhad; Ali Morovati Sharifabadi; Habib Zare Ahmadabadi; Ahmad Jafarnejad Chaghooshi (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The purpose of this paper is to demonstrate systematic application of grounded theory to understand strategic agility in knowledge-based companies (KBCs) in Iran and to explain relationships between them. Methodology: This study uses mixed methods research to explore the determinants of strategic agility in KBCs. This study uses mixed methods approach. Qualitative analysis using "Paradigm model" of grounded theory for data analysis. In Quantitative stage, Structural equation modeling with partial least square is used. Findings: The results of the first phase of the study revealed that causal conditions affecting strategic agility were organizational and environmental factors. As well, intervening conditions included Facilitating and Deterring role of intrinsic attributes of companies; and contextual conditions encompassed Limiting and Encouraging factors. Moreover, strategies and practices were comprised of Extra-organizational and Intra-organizational practices and consequences of strategic agility were consequences at macro and organizational level. The results of the quantitative study, as the second phase, correspondingly confirmed factors identified at the qualitative phase and demonstrated that the casual conditions explain 58.2% of the variance in strategic agility, the three independent constructs explain 72.9% of the variance in strategies, and the strategies explains 59.1% of the variance of consequences. Research limitations: This study was developed on the basis of opinions of a limited number of individuals which could reduce theoretical generalizability of the results. Another limitation is that the research data are limited to KBCs in Iran. Value: The results of this study would theoretically complement the body of knowledge about KBCs which can be cited in future research. Furthermore, the mixed methods approach offers a better insight in understanding strategic agility in KBCs vs the use of either a qualitative or quantitative method alone.
Keywords: 650; strategic agility; knowledge-based company; grounded theory; structural equation modeling